Communication : then and now - Nelson, Robin, 1971- (Minneapolis, MN : Lerner Publications, 2003)
Presents a brief look at how communication has changed over the years.
Includes index.
School Library Journal.
3.3.
3.3
K-3
Keywords: Communication -- United States -- History -- Juvenile literature; Communication -- History; Communication -- History